Politics and Aesthetics in European Baroque and Classicist Tragedy - Bloemendal, Jan; Smith, Nigel (Drama and Theatre in Early Modern Europe, 2016)
Politics and Aesthetics in European Baroque and Classicist Tragedy is a volume of essays investigating European tragedy in the seventeenth century, comparing Shakespeare, Vondel, Gryphius, Racine and other vernacular tragedians, as well as neo-Latin dramas by Jesuits and others, and with respect to politics, religion and law. Readership: All interested in European Baroque and Classicist Drama, early modern history and literature, those interested in politics and literature.